Zvonimir Maretić (1921-1989) : the history of discovery of the first European antilatrodectic serum and its preparator in the occasion of the 30th anniversary of his death = Zvonimir Maretić (1921. – 1989.) : povijest otkrića prvoga europskog antilatrodektičkog seruma i njegova priređivača u povodu 30. godišnjice njegove smrti - Buterin, Toni (Array, 2019)
Zvonimir Maretić was the pioneer of the study of venomous animals and plants, toxicology, and tourism medicine. His achievements have been recognized, but insufficiently researched. His work covers a broad range of biomedical sciences: from public health, ecology, and environmental protection, to epidemiology and infectology. Maretić was one of the founding members of the International Society on Toxinology and the Toxicon journal’s first Editorial Board. He was the first in Europe to prepare the antilatrodectic serum and to successfully apply the weever and scorpionfish antiserum on humans. This brief note tries to commemorate the achievements of Maretić, up to now poorly recognized and insufficiently researched.